SP3.1.5 Can Acute Uncomplicated Diverticulitis be managed Ambulatory?. (9th August 2022) - Kronberga, Madara; Hussain, Shaista; Hama, Bawan; McLaughin, Kate; Peter, Mark; Saha, Arin
Abstract: Introduction: The most common complication of diverticulosis is diverticulitis, which can be described as complicated or uncomplicated if the inflammation is confined to the bowel wall and/or pericolonic fat. Acute uncomplicated diverticulitis (AUD) is traditionally managed by inpatient admission for bowel rest, intravenous fluids and intravenous antibiotics. However, newest World Society of Emergency Surgery (WSES), ACPGBI and NICE guidance suggest that AUD should be managed in ambulatory setting. Aims: To establish if Calderdale and Huddersfield NHS Foundation Trust is complaint with national standards and if this can be carried out safely. Methods: Retrospective data collection of patients diagnosed with AUD between June and August 2021. Inclusion criteria used: CT proven AUD, age <80, patient able to tolerate oral intake, have full capacity and be immunocompetent. Results: 69 patients were diagnosed with acute diverticulitis between June and August 2021. 31 of these patients matched inclusion criteria, with 17 been treated as inpatient (IP) and 14 as outpatient (OP). The average length of hospital stay was of 24h for IP vs 4, 5h for OP. The average deprivation index for IP was 16891 vs 15961 for OP. From the OP group, 2 patients re-presented in hospital, however, none of them needed admission. Conclusions: Our results show that despite our low compliance with national standards (45%), patients with AUD can be safely managed in OP setting with low risk of re-admission. Additionally, by improving our compliance, Trust resources could be saved and bed pressures alleviated without compromising patient safety.